Beiträge zur Insektenfauna der DDR: Hymenoptera - Scolioidea. - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1974)
In the order established for this series, a key to this superfamily is given, followed by a faunistic part with description, nomenclature, biology, distribution and occurence in the districts of the GDR. It is the first comprehensive study of this kind made for the GDR. It covers 20 species, two of which have yet to be found on this territory.